C09 SCAS genes as disease modifiers in huntington's disease. (September 2018) - Peluso, Silvio; Natale, Gemma; Salvatore, Elena; Maio, Luigi Di; Lucia, Natascia De; Roca, Alessandro; Bellofatto, Marta; Russo, Cinzia Valeria; Rosa, Anna De; Criscuolo, Chiara; Santorelli, Filippo Maria; Michele, Giuseppe De
Abstract : Introduction: Huntington's disease (HD) is an autosomal dominant neurodegenerative disease, caused by the expansion of a CAG repeat within exon 1 of IT15 gene. HD exhibits the typical phenomenon of genetic anticipation and the symptoms of the disease appear earlier and more severe in subsequent generations due to meiotic instability. The CAG repeat accounts only for approximately 56%–70% of the variation in age at onset in HD. It is likely that modifying genetic variations, which segregate independently from the primary mutation, could influence the age at onset. Aims of the study: Genetic, pathological, and clinical similarities exist between HD and spino-cerebellar ataxias (SCAs). In this study, seven SCAs genes have been studied as modifiers of age at onset in a cohort of HD patients. Materials and Methods: We enrolled 50 HD patients. For every HD subject, CAG repeats have been measured on the larger allele of ATXN1, ATXN2, ATXN3, CACNA1A, ATXN7, PPP2R2B, and TBP genes. Regression analysis was used to evaluate the effects of CAG repeats in SCAs genes on age at motor, cognitive and psychiatric onset in HD patients. Results: We did not find extensive correlations between CAG repeats in SCA genes and age at onset of HD. The only exceptions were represented by ATXN2 and CACNA1 genes for age at motor onset, and ATXN2 for age at psychiatric onset. When a multiple regression model was tested, a small additional effect on age at motor onset was identified only for CACNA1A. CAG repeats in expanded HD gene and larger CACNA1A alleles account for 64% of age at motor onset in HD patients. Conclusions: CACNA1A gene could represent a mild genetic modifier of age at onset in HD patients. Further studies, conducted on larger HD patients' cohorts, are needed to confirm our data.